Co-self-assembly of multiple DNA origami nanostructures in a single pot. Issue 39 (15th April 2021) - Johnson, Joshua A.; Kolliopoulos, Vasiliki; Castro, Carlos E.
Abstract : We demonstrate co-self-assembly of two distinct DNA origami structures with a common scaffold strand through programmable bifurcation of folding pathways. Abstract : Simultaneous self-assembly of two distinct DNA origami nanostructures folded with the same scaffold strand was achieved in a single pot. Relative yields were tuned by adjusting concentrations of the competing strands, correlating well with folding kinetics of individual structures. These results can faciliate efficient fabrication of multi-structure systems and materials.